Scrotal siliconoma: complications of an unapproved substance to an uninformed public - Sepehripour, Sarvnaz (BMJ Publishing Group, 2013)
Liquid silicone is not approved for cosmetic injections in the USA and the UK because of possible adverse reactions. Despite this ban it is, unfortunately, still used by unlicensed practitioners and is offered to an uninformed public. This case report presents a case of scrotal siliconoma in a patient who received a liquid silicone injection for scrotal augmentation in an unlicensed practice in London and developed complications. The case should serve as a warning and encourage more patient education and public awareness about the dangers of liquid silicone injection.